Teacher Personality Competence In Building The Character Of Students - Opan Arifudin; Hafiz Raza Ali (Lafadz Jaya Publisher, 2022)
This study aims to determine and analyze the teacher's personality competence in fostering the character of students. This research is qualitative research with a case study method. The results of this study indicate that the teacher's personality competence at schools is good. Teachers already understand the competence of a teacher's personality. Mastery of personality competency indicators has been carried out in accordance with what is stipulated by the government in the Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers, that at least the personality competencies that must be possessed by a teacher include faith and piety, noble character, wisdom and wisdom, democratic, steady personality, stable and mature, authoritative, honest, sportsmanship, be a role model for students, evaluate themselves and develop themselves independently and sustainably. Most teachers already have these personality competencies, and then they try to continue to develop their personality competencies in order to become professional teachers in carrying out their duties and responsibilities.